PENDIDIKAN ISLAM DI ERA MILENIAL - Abuddin Nata (Conciencia, 2018)
Today humans live in the millennial era. The era that is a continuation of this global era has created new challenges that must be transformed into opportunities that can be put to good use, so that challenge brings a blessing for everyone to do. Since the millennial era besides having similarities also has differences, especially in the use of digital technology that goes beyond the computer era, this kaeadaan has invited a number of experts to speak out and at the same time offer a number of thoughts and ideas in dealing with it. Islamic education with various types and levels, ranging from traditional pesantren that is non-formal, hinggapesantren modern with various programs, ranging from kindergarten to college, is institutionally part of the national education system. With such a position, Islamic education will inevitably have to contribute, even responsible menak prepare human beings in the millennial era. That is a human being who is able to change challenges into opportunities, and can use them for his own material and spiritual welfare. This paper seeks to explore the potential contained in Islamic education with various types and levels in the face of challenges in the millennial era. This paper begins by presenting the characteristics and challenges of the millennial era, social problems and their impact on life.